Alzheimer's disease: the amyloid hypothesis and the Inverse Warburg effect - Demetrius, Lloyd A.; Magistretti, Pierre J.; Pellerin, Luc (Frontiers in Physiology, 2015)
Epidemiological and biochemical studies show that the sporadic forms of Alzheimer’s disease (AD) are characterized by the following hallmarks : (a) An exponential increase with age ; (b) Selective neuronal vulnerability ; (c) Inverse cancer comorbidity. The present article appeals to these hallmarks to evaluate and contrast two competing models of AD : the amyloid hypothesis (a neuron-centric mechanism) and the Inverse Warburg hypothesis (a neuron-astrocytic mechanism). We show that these three hallmarks of AD conflict with the amyloid hypothesis, but are consistent with the Inverse Warburg hypothesis, a bioenergetic model which postulates that AD is the result of a cascade of three events – mitochondrial dysregulation, metabolic reprogramming (the Inverse Warburg effect), and natural selection. We also provide an explanation for the failures of the clinical trials based on amyloid immunization, and we propose a new class of therapeutic strategies consistent with the neuroenergetic selection model.